Genetics, Host Range, and Molecular and Pathogenic Characterization of Verticillium dahliae From Sunflower Reveal Two Differentiated Groups in Europe - Martín-Sanz, Alberto; Rueda, Sandra; García-Carneros, Ana B.; González-Fernández, Sara; Miranda-Fuentes, Pedro; Castuera-Santacruz, Sandra; Molinero-Ruiz, Leire (Frontiers in Plant Science, 2018)
Verticillium wilt and leaf mottle of sunflower, caused by the fungus Verticillium dahliae (Vd) has become a major constraint to sunflower oil production in temperate European countries. Information about Vd from sunflower is very scarce despite genetics, molecular traits and pathogenic abilities of fungal strains affecting many other crops being widely known. Understanding and characterizing the diversity of Vd populations in those countries where sunflowers are frequent and severely affected by the fungus are essential for efficient breeding for resistance. In this study, we have analyzed genetic, molecular and pathogenic traits of Vd isolates affecting sunflower in European countries. When their genetics was investigated, almost all the isolates from France, Italy, Spain, Argentina, and Ukraine were assigned to vegetative compatibility group (VCG) 2B. In Bulgaria, Turkey, Romania, and Ukraine, some isolates were assigned to VCG6, but some others could not be assigned to any VCG. Genotyping markers used for Vd affecting crops other than sunflower showed that all the isolates were molecularly identified as race 2 and that markers of defoliating (D) and non-defoliating (ND) pathotypes distinguished two well-differentiated clusters, one (E) grouping those isolates from Eastern Europe and the other (W) all those from the Western Europe and Argentina. All the isolates in cluster W were VCG2B, while the isolates in cluster E belonged to an unknown VCG or to VCG6. When the host range was investigated in the greenhouse, the fungus was highly pathogenic to artichoke, showing the importance of farming alternatives in the management of Verticillium attacks. Sunflower genotypes were inoculated with a selection of isolates in two experiments. Two groups were identified, one including the isolates from Western Europe, Argentina, and Ukraine, and the other including isolates from Bulgaria, Romania, and Turkey. Three pathogenic races were differentiated: V1, V2-EE (Eastern Europe) and V2-WE (Western Europe). Similarly, three differentials are proposed for race identification: HA 458 (universal susceptible), HA 89 (resistant to V2-EE, susceptible to V2-WE) and INRA2603 (susceptible to V2-EE, resistant to V2-WE). The diversity found in Vd affecting sunflower must be taken into account in the search for resistance to the pathogen for European environments of sunflower production.